Comparison of Results of Atypical Lymphocyte Test, RT-PCR and ELISA Using Recombinant Multivalent Envelope Protein Domain III (ED-III) Dengue Virus in Dengue Fever Patients - Inayati, Nurul; Fihiruddin, Fihiruddin; Ernawati, Sri; Unsunnidhal, Lalu; Jannah, Raudatul (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Prevention of the transmission of dengue hemorrhagic fever (DHF) is carried out by breaking the chain of dengue transmission and administering vaccines, but to date, this has not achieved the expected target. Dengue virus tests using RT-PCR require skills and relatively expensive equipment. Serological test of IgM and IgG often shows false negatives or false positives, especially in dengue-endemic areas. The antibody test against NS1 using the ELISA method has weaknesses because anti-dengue IgM is often not detected in secondary infections. The development of serodiagnostic tests for rapid, affordable, sensitive, and specific detection of dengue virus infection is very necessary. Recombinant multivalent envelope proteins domain III (ED-III) dengue virus is a biomarker that has the potential to be developed to detect all dengue virus serotypes. One of the proteins that has high antigenicity is glycoprotein E which is found in the envelope of the dengue virus and is the most antigenic part of the virus. This research aims to combine several parts of the antigenic protein found in all dengue virus serotypes as immunoserodiagnostic material. This research is an analytical survey research, that compares the results of the atypical lymphocyte test, RT-PCR, and ELISA using the multivalent ED-III antigen. The number of samples used was 26 samples obtained from patients who were diagnosed with dengue fever using an accidental sampling technique. The results of the atypical lymphocyte examination showed 14 positive samples, while the results of the RT-PCR and ELISA examinations were 23 and 24 positive respectively. The average Optical density (OD) of examination using the ELISA method was 1.902 with sensitivity and specificity levels of 92% and 96%. There is no difference result of the RT-PCR compared with the ELISA test. Therefore, recombinant multivalent envelope protein domain III (ED-III) dengue virus can be used as a diagnostic tool to detect dengue fever infection.